Applicability of the InSAR technique for slope monitoring - Coutinho, Roberto Quental; Alves, Jailson Silva; de Araújo Falcão Moreira, Hanna Barreto; Pontes, Júlia Isabel [UNESP]; Júnior, Wilson Ramos Aragão (ABMS - Brazilian Association for Soil Mechanics and Geotechnical Engineering, 2023)
Interferometry is a technique that can be applied to SAR (Synthetic Aperture Radar) images that allow obtaining Digital Elevation Models, displacement measurements and assistance for monitoring large areas and/or engineering constructions. The objective of this paper is to present aspects related to the technique of Interferometry SAR (InSAR) applied to the monitoring of slopes. To do so, a systematic bibliographical review was used, through research platforms in scientific collections, in order to highlight the functioning and method of operation of InSAR. Besides that, the practical experience of the authors contributed to a critical analysis of the remote sensing technique addressed. The results show theoretical aspects related to the operation of SARs on board satellites, highlighting their characteristics, orbital systems, types of imaging geometry, as well as the principles of interferometric processing of SAR images. Practical applications demonstrate the potential of InSAR with an emphasis on slope monitoring, highlighting its ability to acquire topographic information on a millimeter scale, monitoring the long-term temporal evolution of displacements, the possibility of composing a monitoring system allowing directing the implementation of other instruments for evaluating the in situ conditions and some limitations regarding the time interval (satellite revisit time) for the acquisition of the displacement data.
Keywords: Geotechnical monitoring; Interferometry; Remote sensing; Synthetic Aperture Radar